Radioactivity levels in beach sand from Hambantota to Dondra, Sri Lanka - Bandara, W.M.R.C.; Mahawatte, P. (General Sir John Kotelawala Defence University, 2015)
This study aims to evaluate the activity concentrations of 232Th, 238U and 40K in beach sand along the southern coastal strip from Hambantota to Dondra, Sri Lanka. The results of this study serve as a database for radioactivity levels of the mineral sand deposits in the selected strip. It will also provide information about unidentified locations having sand with high radioactive mineral content. This is an extended study of an ongoing project to determine the above three radionuclides in the coast line of Sri Lanka. Sand samples collected from 38 locations along the beach from Hambantota to Dondra were analyzed for 232Th, 238U and 40K radionuclide content using high resolution gamma ray spectrometry. The resulting concentrations for 232Th, 238U and 40K ranged from 1.4 0.7 – 10752 203, 4 0.6 – 1726 41, and 54 5 – 852 57 Bq kg-1 respectively. The minimum detection limits of the system for the three radionuclides were 0.9, 0.3 and 5.4 Bq kg-1 respectively. The percentages of the samples having the activity concentration below the worldwide average for 232Th, 238U and 40K in soil were 34%, 47% and 92%. Thorium to uranium ratio in sand samples collected in this study ranged from 0.17 to 7.88. The activity level measured in this study is comparable with the activity levels measured in previous studies done in the other areas of the coastline of Sri Lanka. Four new locations (Nilwella (5°57'54.8"N 80°43'03.3"E), Polgahamulla (5°57'28.3"N 80°39'54.1"E), Unukuruwella (6°00'17.7"N 80°46'02.7"E) and Wellamadama (5°55'53.6"N 80°34'56.0"E)) with sand having high radionuclide content were identified.
Keywords: Sri Lanka; Beach Sand; Radioactivity